Drs. Abdul Ghani Azmi Bin Idris: Tinjauan Terhadap Sumbangan dan Penulisan Beliau dalam Majalah Pengasuh Mengenai Ilmu Hadith - Abdul Hamid, Faisal @ Ahmad Faisal (Jurnal Usuluddin, 2007)
Majalah Pengasuh has produced variety of articles on Islam written by local and international scholars ever since its early publication. Drs Abdul Ghani Azmi was among the earliest writters who composed on al-Hadith in Prophet Traditions Column provided in the Majalah Pengasuh. His efforts and deep interest on al-Hadith has brought him to be appointed as Majalah Pengasuhs Author in Chief. The chances given to him had encouraged him to write more on this discipline. Thus, this article attempts to discuss Drs Abdul Ghani Azmis biodata, his scholarship in al-Hadith discipline together with his works in Majalah Pengasuh.